Gender difference in the acute influence of a 2-hour run on arterial stiffness in trained runners - Nieman, D.; Dew, D.; Krasen, P. (Research in Sports Medicine, 2013)
Arterial stiffness scores over a 5-h period following a 2-h run were measured in trained males (N = 8, age 39.3 ± 2.3 y) and females (N = 8, 35.8 ± 2.8 y). Subjects reported for two lab sessions (randomized, crossover design) from 7:30 am to 4:15 pm, separated by 1-2 weeks, and either rested or ran for 2 h on a treadmill at 75% VO2max from 9:15 to 11:15 am. Augmentation index standardized to a heart rate of 75 bpm (AIx75), and carotid to femoral pulse wave velocity (PWV), were measured by applanation tonometry. Significant interaction effects were measured for AIx75 (P = 0.039) and PWV (P = 0.020), and compared with the rest condition, female runners experienced decreased AIx75 from 11:45 am to 3:15 pm, and in PWV at 11:45 am and 12:15 pm, in contrast to no change in the male runners. These data support a notable gender difference in arterial stiffness following a 2-h bout of running.